2016
DOI: 10.4103/2249-4863.197309
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of domestic violence and its associated factors among married women in a rural area of Puducherry, South India

Abstract: Background:Violence against women is an emerging problem worldwide and more so in India. Considering its adverse effects on women's health, assessing the burden of violence in the community will help in planning services for the victims.Objectives:To determine the prevalence of domestic violence and to identify factors associated with domestic violence among married women in reproductive age group in rural Puducherry.Materials and Methods:A community-based cross-sectional study was carried out in a rural area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 8 publications
1
19
0
1
Order By: Relevance
“…11 Other studies have reported that domestic violence is associated with a low education level. 12 - 15 . As can be seen in the results of this study, a low level of education is associated with domestic violence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Other studies have reported that domestic violence is associated with a low education level. 12 - 15 . As can be seen in the results of this study, a low level of education is associated with domestic violence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature suggest that there is an important relationship between early marriage age and domestic violence. 1 , 12 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…Non-Muslims women were 0.12 times less likely compared to Muslims (AOR = 0.12, CI = 0.03-0.51, p = 0.004), and employed women were 0.56 times less likely compared to unemployed or housewife (AOR = 56, CI = 0.30-1.06, p = 0.075) to experience IPV. Women with educated husband were 0.06 times less likely to experience IPV compared to women with uneducated husband (AOR = 0.06, CI = 0.01-0.53, p = 0.011 High prevalence of IPV was also reported in many other countries in recent studies, 42% in Malawi (Chikhungu et al, 2019), 56.7% in Sothern India (George et al, 2016), 40% in Gambia (Jabbi et al, 2020), 42.7% in Zimbabwe (Lasong et al, 2020), and 32.5% in Haiti (Occean et al, 2020). Gebrewahd et al (2020) conducted a survey amid COVID-19 pandemic in northern Ethiopia, and found the prevalence of IPV 24.6%, where EV = 13.3%, PV = 8.3%, and SV = 5.3%.…”
Section: Prevalence and Risk Factors Of Ipvmentioning
confidence: 72%
“…(Puducherry; South India, 2015), and Singh and Shukla (NFHS-3). [1141516] This might be because education can change the way of thinking. Alcoholic husband was a risk factor in both types of domestic violence.…”
Section: Discussionmentioning
confidence: 99%